(untitled) (Research, Society and Development, 2020)
The semiarid region presents a wide range of plant species, among them Luetzelburgia auriculata (Allemão) Ducke (pau-mocó) is a medium-sized tree, predominant in the Caatinga biome and that carries out a fundamental role for the local ecosystem. The aim was to describe and illustrate the morphological characteristics of fruits, seeds and plantlents of this species. The fruits/seeds were reap from a hub tree in the city of Boa Ventura - PB and 100 units were used for biometric description. Regarding the characterization of germination and plantlents morphology, 100 seeds were sown and the stages were monitored for 30 days. The fruit is of the samara type, dry, indehiscent, glabrous and brown in color, with an only one seed. The length is 71.28 mm; width 26.76 mm; thickness of 1.24 mm and an average weight of 0.73 g. The seeds are exalbuminous, with fine tegument and lateral circular hilum, small and whitish. The length is 17.62 mm; width 9.89 mm; 4.37 mm thickness and 0.36 g unit weight. Germination is of the epigeal type, with the radicle emission on the third day after sowing, breaking the tegument nearby the hilum. The pau-mocó plantlets characterize the post-seminal development of the PER type (epigeal-phanerocotyledon, with reserve cotyledons). The morphological aspects described and illustrated showed to be homogeneous and provide information for species recognition in the early stages of development.